Aplikasi Layanan Perbaikan Motor Online Berbasis Android dengan Memanfaatkan Google Maps - Faiz Ataka Ubaidillah; Anita Fira Waluyo (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
AHASS Mitra Rasa Motor is a business that operates in the field of motorbike repair services, its existence is really needed by Honda motorbike users to carry out maintenance or repairs on their vehicles. The services provided at AHASS Mitra Rasa Motor are only in workshops and do not accept repair services at consumer locations. In order to provide good and satisfying service, an Android-based online motorbike repair service application was created using Google Maps. In the research the author used the Waterfall method. This method includes system analysis, system design, implementation and testing. This Android-based online motorbike repair service application using Google Maps was built using the PHP, HTML, JavaScript, Kotlin and MySql database programming languages. The results of this research succeeded in creating an Android and Website based system where from the Android application system used by consumers they can carry out order transactions which will then be entered into the database and displayed on the Website application system. Apart from that, there are test results using the BlackBox method